Mixed forests plantations with naturalized broadleaves and nitrogen fixing species - Monteiro, Maria do Loreto (2010)
Over the last three decades there is a renewed and growing interest in the mixed plantations and, when site conditions allow, in the gradual change from pure to mixed stands. To these stands are attributed valuable functions because they are much more natural, sustainable and stable, with a big diversity and they improve the landscape aesthetics. The aim is to study the possible benefits among the production of the main species, when in the presence of Nfixing species